2023
DOI: 10.3389/fspor.2022.981755
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Effect of low energy availability and training load on sleep in a male combat sport athlete

Abstract: PurposeThe aim of this case report was to describe the sleep responses in a male combat sport athlete, who was engaging in both chronic (CWL) and acute (AWL) weight loss practices in order to reduce body mass for a national competition.MethodsDuring the first seven weeks of training (Phases 1 and 2), the athlete adhered to a daily energy intake (EI) equating to their resting metabolic rate (1700 kcal·day−1) followed by a reduction in EI (1200–1300 kcal·day−1) in the 5 days before weighing in (Phase 3). Nocturn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Occasionally, athletes may be in a state of low energy availability (e.g., sudden decrease of energy intake in case of weight loss). A case study reported that weight loss practices did not compromise the sleep of martial sports athletes ( 12 ). Research on sleep patterns of athletes during the early coronavirus disease lockdown showed that sleep quality and quantity were characterized as “normal” for half of them, followed by those reporting “improved” and “worsened” sleep ( 13 ).…”
Section: Sleep and Athletesmentioning
confidence: 99%
“…Occasionally, athletes may be in a state of low energy availability (e.g., sudden decrease of energy intake in case of weight loss). A case study reported that weight loss practices did not compromise the sleep of martial sports athletes ( 12 ). Research on sleep patterns of athletes during the early coronavirus disease lockdown showed that sleep quality and quantity were characterized as “normal” for half of them, followed by those reporting “improved” and “worsened” sleep ( 13 ).…”
Section: Sleep and Athletesmentioning
confidence: 99%
“…However, this study only used a subjective assessment of sleep quality among a limited number of participants ( n = 13). Thomas et al [ 28 ] explored sleep patterns over a prolonged period of time, including chronic (8 weeks: phases 1 and 2) followed by acute (5 days: phase 3) weight loss practices in a case report concerning a taekwondo athlete. They found a decrease in total sleep time (TST) but an increase in SE during the third phase compared to phases 1 and 2.…”
Section: Introductionmentioning
confidence: 99%
“…These practices can be dangerous to health and are strongly discouraged [ 8 ]. Both chronic and acute weight loss practices are seen in the training phase of boxers and were in a state of LEA during the entire training period in the previous study [ 9 ]. There are no studies reported with respect to the ES of Indian boxers.…”
Section: Introductionmentioning
confidence: 99%